Special Issue "Talent Identification and Development in Youth Sports" - Adam Leigh Kelly; Alberto Lorenzo Calvo; Sara Diana Leal dos Santos; Sergio Lorenzo Jiménez Sáiz (MDPI AG, 2022)
We are delighted to share our Special Issue on Talent Identification and Development in Youth Sports [...]